Fostering Student Character: The Implementation of Tazkiyatun Nafs Philosophy in Elementary Education - Zainuddin; Herdiana; Ratna Sari; Iskandar (Al-Qalam Institue, 2026)
This study aims to examine the implementation of the philosophy of Tazkiyatun Nafs in fostering students' moral character Elementary Education to explore how its principles are translated into educational practices. The research employed a qualitative approach using a case study design. Data were collected through classroom observations, semi-structured interviews with the principal, teachers, and students, as well as document analysis. The data were analyzed using the interactive model of data condensation, data display, and conclusion drawing and verification. The findings reveal that the philosophy of Tazkiyatun Nafs is implemented through the integration of religious habituation, teacher role modeling, reflective learning, and a school culture grounded in Islamic values. These practices encourage students to internalize moral values, strengthen spiritual awareness, and develop positive behaviors such as honesty, discipline, responsibility, empathy, and respect. The study further demonstrates that sustainable moral development is achieved when spiritual purification becomes the foundation of educational activities rather than merely emphasizing behavioral compliance. The findings provide both theoretical and practical implications by positioning Tazkiyatun Nafs as an operational framework for character education and offering valuable insights for educators and policymakers seeking to strengthen morally and spiritually grounded educational practices.